Biological diversity and similarity indices of fish species in Erinle River, Osun State, Nigeria - Adams O. Iyiola (The Proceedings of the Nigerian Academy of Science)
This study assessed the fish species composition, abundance, and biodiversity indices of two major reservoirs in Osun State, Nigeria, namely, Owalla Reservoir (OWR) and Erinle Reservoir (ERR). A total of 1,248 individual fish, comprising 25 species from 10 families, were identified across both reservoirs. OWR exhibited significantly higher fish abundance (82.9%) compared to ERR (17.1%). Oreochromis niloticus and Coptodon zilli were the dominant species in OWR and ERR, respectively. Despite differences in abundance, both reservoirs recorded similar species richness (15 species each). Cichlids were the most prevalent group, representing over half of the species in both reservoirs. Biodiversity indices revealed that ERR had a higher Shannon-Wiener diversity index (H = 2.209), suggesting greater species diversity and ecological stability compared to OWR (H = 1.8), which had a lower Simpson's index value (0.0), indicative of lower pollution levels. The evenness index was also higher in OWR (0.7), implying a relatively balanced species distribution. Similarity indices (Sørensen's and Jaccard's) indicated limited community overlap between the two reservoirs, with only four species common to both. Various ecological and anthropogenic factors, including reservoir location, upstream-downstream dynamics, and local fishing activities, influence the observed patterns of diversity. The findings underscore the ecological importance of these reservoirs while also highlighting potential areas of environmental stress and biodiversity loss.